Comparison of Animal Serum-Free Media Culture for cGMP-Compliant Mesenchymal Stem Cell Expansion - Irawan, Risky Chandra Satria; Zakiyah, Nibras; Aji, Bramassetyo; Budiarto, Bagus Aji (International Journal of Cell and Biomedical Science, 2025)
Background: Mesenchymal stem cells (MSCs) are multipotent stromal cells distinguished by their ability to self-renew, their potential for multilineage differentiation, and their strong immunomodulatory characteristics. The recent in vitro expansion of MSCs primarily relies on culture media that is supplemented with fetal bovine serum (FBS). Although FBS is effective in enhancing the proliferation of MSCs and ensuring their survival, its use poses several notable challenges, particularly in clinical environments. Methods: This study seeks to fill this important gap by conducting a comprehensive comparison of various commercially available animal source-serum free media formulations against traditional FBS-supplemented media for the expansion of umbilical cord-derived mesenchymal stem cells (UC-MSCs). The morphology and density of the cells were examined using an inverted microscope. The cell surface of UC-MSCs was analysed through flow cytometry. The evaluation of cytokines released by UC-MSCs was carried out using ELISA. Result: The conditioned medium obtained from UC-MSCs cultured in HPL shows increased levels of exosomes and anti-inflammatory cytokines. Moreover, the UC-MSCs cultured in HPL-supplemented medium maintained a normal morphology and exhibited expression of UC-MSC surface markers exceeding 95%. Additionally, HPL enhanced the proliferation of UC-MSCs to eight times the cell number on the day of seeding. Conclusion: Media enriched with HPL presents considerable potential for future applications within the pharmaceutical sector.